The scientific method: Computing the future. (Economist, 2006)
Research conducted by a team of scientists led by Stephen Emmott of Microsoft Research in Cambridge, England, has found that, in addition to helping scientists with their work, computing and its concepts, theorems, and tools have become integrated into the very fabric of science. The team's report, “Towards 2020 Science,” published in a March 2006 edition of Nature, predicts a science revolution of similar proportions to that triggered by the construction of the first telescope or the invention of calculus. Microsoft Research Cambridge has announced that it will provide £2.5 million ($3 million) in funding to research that deals with the policy areas discussed in the report.